Gonadotropin-Releasing Hormone Agonist Combined with Hormone Replacement Therapy Protocol Improves the Live Birth Rate in Frozen-Thawed Embryo Transfer Cycles for Patients without Endometriosis - Yu Wang; Huixia Xie; Ping Shen; Qun Lv (IMR Press, 2023)
Background: Whether gonadotropin-releasing hormone agonist (GnRH-a) pituitary suppression improves clinical outcomes in non-endometriosis patients undergoing frozen embryo transfer remains controversial. The objective of this study is to investigate whether GnRHa combined with hormone replacement treatment (HRT) compared to HRT alone can improve the clinical outcomes of frozen-thawed embryo transfer in patients without endometriosis. Methods: This is a retrospective cohort study. This study involved 2178 frozen-thawed embryo transfer (FET) cycles of non-endometriosis patients between January 2018 and December 2019, of these cycles, 1535 were GnRHa-HRT combined cycles and 643 were HRT alone cycles. The primary outcomes were the clinical pregnancy and live birth rates. SPSS software (version 23.0, IBM Corp., Chicago, IL, USA) was used for data analysis. Results: Single-factor analysis showed that the live birth and implantation rates -were higher in the GnRHa-HRT group than those in the HRT group (p < 0.05). The mid-to-late-term miscarriage rate in the GnRHa-HRT group was lower than that in the HRT group (p < 0.05). The rates of human chorionic gonadotropin (HCG) positivity, clinical pregnancy, early abortion, multiple pregnancy, and preterm delivery between the two groups were comparable. Multivariate logistic regression analysis showed that rate of the live birth in the GnRHa-HRT group was higher than in the HRT group (p = 0.009), and there was no significant difference in the clinical pregnancy rate between the two groups (p = 0.103). Conclusions: This large-scale retrospective study revealed that non-endometriosis women in FET cycles may benefit from the GnRHa downregulation due to increasing the live birth rate.